REDESAIN KEMASAN KOTAK KOPI BUBUK SURYA DI DAIRI, SUMATERA UTARA - HUSNI SIHHAH ANGKAT, Hendra Afriwan, S. Sn., M. Sn Yofita Sandra, S.Pd., M.Pd. (DEKAVE : Jurnal Desain Komunikasi Visual, 2015)
box with the view that a more simple but visible exclusive. (2) To designcoffee box who unique so capable attract consumer interest for buy Kopi Bubuk Surya product. The file of designing media this promotion is with doingobservation and interviews into the company. Outcome works of end the form of packaging as the the main media, introduced excellence and enjoyment the results of the products in this packaging and the part of important information enterprise.Keywords: Kopi Bubuk Surya, promotion, Packaging.